A Visual Method in Expressing Junior High School Students' Voice Towards Literacy - Nur Arifah Drajati; Rizka Junhita; Bunga Ikasari (Universitas Islam Negeri (UIN) Mataram, 2020)
Visual methods are well known in the education research field but rarely used in junior high school, where students' voices are needed to explore the education needs. In this article, the researchers intend to accomplish one fundamental objective. The key objective is to emphasize that photovoice as a visual method can build good engagement for students in learning activities and promote students' voices about how the learning process takes place and what the students are thinking about that process, which is useful in supporting learning activities. Here, the researchers use photovoice as the methodology. The author collected and analyzed the data using SHoWeD. This article, therefore, to expand knowledge about visual methods as methodological innovation in learning research.